Polarisation of the auroral red line in the Earth's upper atmosphere: a review (Invited) - Lamy, H.; Barthelemy, M.; Lilensten, J.; Bommier, V.; Simon Wedlund, C. (HAL CCSD, 2013)
International audience Polarisation of light is a key observable to provide information about asymmetry or anisotropy within a radiative source. Polarimetry of auroral emission lines in the Earth's upper atmosphere has been overlooked for decades. However, the bright red auroral line (6300Å) produced by collisional impact with electrons precipitating along magnetic field lines is a good candidate to search for polarisation. This problem was investigated recently with observations obtained by Lilensten et al (2008), Barthélemy et al (2011) and Lilensten et al (2013) with a photopolarimeter. Analysis of the data indicates that the red auroral emission line is polarised at a level of a few percent. The results are compared to theoretical predictions of Bommier et al (2011) that were obtained for a collimated beam. The comparison suggests the existence of depolarization processes whose origin will be discussed. A new dedicated spectropolarimeter currently under development will also be presented. This instrument will cover the optical spectrum from approximately 400 to 700 nm providing simultaneously the polarisation of the red line and of other interesting auroral emission lines such as N2+ 1NG (4278Å), other N2 bands, etc. The importance of these polarisation measurements in the context of upper atmosphere modelling and geomagnetic activity will be discussed. Lilensten, J. et al, Polarization in aurorae: A new dimension for space environments studies, Geophys. Res. Lett., 26, 269, 2008 Barthélemy M. et al, Polarisation in the auroral red line during coordinated EISCAT Svalbard Radar/optical experiments, Annales Geophysicae, Volume 29, Issue 6, 2011, 1101-1112, 2011. Bommier V. et al, The Theoretical Impact Polarization of the O I 6300 Å Red Line of Earth Auroræ, Annales Geophysicae, Volume 29, Issue 1, 2011, 71-79, 2011 Lilensten, J. et al, The thermospheric auroral red line polarization: confirmation of detection and first quantitative analysis, Journal of Space Weather and Space Climate, Volume 3, 12, 2013.